ANALISIS PENERAPAN INTEGRATED MARKETING COMMUNICATION PADA SOCIAL BUSINESS : Studi Deskriptif pada PT. YOT Inspirasi Nusantara - Dini Oktaviani (2021)
Social business is a business that does not make material profit as the axis of its activities, but rather focuses on non-commercial social action. This business has a core value in changes and can be based on youth movement, environmental issue, entrepreneurship, etc. However, accurate communication strategies are still needed to promote the values/goals and the desired forms of change, so people are willing to do it. Therefore, this study contains the application of Integrated Marketing Communication at PT. YOT Inspirasi Nusantara as an example of a social business that successfully implemented it. The method used in this research is descriptive qualitative method, with data collection techniques in the form of interviews. The results of this study provide insights about the application of Integrated Marketing Communication at PT. YOT Inspirasi Nusantara. PT. YOT Inspirasi Nusantara uses eight elements of Integrated Marketing Communication consisted public relations, publicity, direct marketing, advertising, internet marketing, sponsorships, and individual sales. Researcher suggest that PT. YOT Inspirasi Nusantara needs to be more balance on the portion for each promotional mix that they used. The concept of Integrated Marketing Communication is also need to be developed inclusively in all social businesses in Indonesia, regarding to the rapid development of technology now on. And the last, the community is expected to contribute more on the development of social business in Indonesia, because the social businesses are also need to be more recognized in order to be settle and create a better a change to the society per se.